"Development of Body, Mind, and Soul:" Paramahansa Yogananda's Marketing of Yoga-Based Religion. Issue 1 (8th March 2019) - Neumann, Dave J.
ABSTRACT: As founder of a religious movement emphasizing soteriological goals, Paramahansa Yogananda is at odds with the prevailing scholarly portrayal of yoga as a modern, syncretic bodily practice focused on mindfulness and physical well-being that, even when employing language of transcendence, magic, or the supernatural, typically has this-worldly perfection in mind. Yogananda, thus, offers an important counterpoint to the dominant historiography of yoga. Whereas more recent "global gurus" often remained in India and recruited among diaspora Indians, Yogananda was the first Indian to establish a thriving yoga-based Hinduism among white converts in the United States. He worked to make his message compelling in the often-hostile milieu of a dominant Christian culture. In this article, I consider Southern California's identity as a "spiritual frontier" that offered a uniquely conducive space to launch a Hindu religious movement in a virulently xenophobic era. I explore Yogananda's vision of the "science of religion, " language that reflected not a materialist reduction of yoga to somatic goals, but a precise, systematic meditation method designed to achieve God-contact. Yogananda offered various products in an effort to build brand loyalty for his yoga-based religion. Although he strategically promoted the very real health and energy benefits of his instruction, the heart of his commercial and spiritual enterprise was a yoga correspondence course that promised to train disciples in a devotional relationship with a God he often depicted as a personal Being. I conclude by examining Yogananda's role as the authoritative divine guru who mediated his religious products to devotees and remained present after his death to guide them toward ultimate bliss.